Adenovirus type 7 associated with severe and fatal acute lower respiratory infections in Argentine children - Misirlian Alicia; Videla Cristina; Carballal Guadalupe; Requeijo Paula V; Aguilar María (BMC, 2002)
Abstract Background Adenoviruses are the second most prevalent cause of acute lower respiratory infection of viral origin in children under four years of age in Buenos Aires, Argentina. The purpose of this study was to analyze the clinical features and outcome of acute lower respiratory infection associated with different adenovirus genotypes in children. Methods Twenty-four cases of acute lower respiratory infection and adenovirus diagnosis reported in a pediatric unit during a two-year period were retrospectively reviewed. Adenovirus was detected by antigen detection and isolation in HEp-2 cells. Adenovirus DNA from 17 isolates was studied by restriction enzyme analysis with Bam HI and Sma I. Results Subgenus b was found in 82.3% of the cases, and subgenus c in 17.7%. Within subgenus b, only genotype 7 was detected, with genomic variant 7h in 85.7% (12/14) and genomic variant 7i in 14.3% (2/14). Mean age was 8.8 ±; 6 months, and male to female ratio was 3.8: 1. At admission, pneumonia was observed in 71% of the cases and bronchiolitis in 29%. Malnutrition occurred in 37% of the cases; tachypnea in 79%; chest indrawing in 66%; wheezing in 58%; apneas in 16%; and conjunctivitis in 29%. Blood cultures for bacteria and antigen detection of other respiratory viruses were negative. During hospitalization, fatality rate was 16.7% (4 /24). Of the patients who died, three had Ad 7h and one Ad 7i. Thus, fatality rate for adenovirus type 7 reached 28.6% (4/14). Conclusions These results show the predominance of adenovirus 7 and high lethality associated with the genomic variants 7h and 7i in children hospitalized with acute lower respiratory infection.